Quality of Life and Supportive Care Needs of Gynecologic Cancer Survivors. (October 2019) - Reb, Anne M.; Cope, Diane G.
Gynecologic cancer survivors experience significant distress that can impact quality of life (QOL). Optimal survivorship care requires an understanding of the survivor's QOL and supportive care needs. The purpose of this study was to describe the QOL and needs of gynecologic cancer survivors. Women with an initial diagnosis of gynecologic cancer within 7 months of completing primary treatment ( N = 34) completed the QOL-Cancer Survivor tool and the Cancer Survivors' Unmet Needs Survey. Fear of cancer recurrence was a repetitive theme for both tools. The lowest ranking QOL items were distress from diagnosis and treatment, family distress, and uncertainty about the future. Commonly reported needs included help to reduce stress, manage side effects, cope with fears of cancer recurrence, and gain reassurance that providers were communicating, and providing the very best medical care. Appreciating QOL and needs can facilitate the development of support services specifically tailored to gynecologic survivors.